An overview of urbanization in ecuador under functional urban area definition - Moises Obaco; Juan Pablo Díaz-Sánchez (REGION, 2018)
This paper explores the urbanization process under Functional Urban Areas (FUAs) definition considering Ecuador as case of study. Analyzing data from 1950 to 2010, we have identified 28 FUAs that confirm that urbanization has rapidly increased in Ecuador since 1962. Then, a slum index, which is constructed using a United Nations methodology, is applied to approach individuals' wellbeing at dwelling level into FUAs for the period 1990 - 2010. We find that the greater improvement in terms of quality of dwelling takes place during the period 1990 - 2001 compared to 2001-2010.
Keywords: R12; R23; 330; Developing economies; Ecuador; FUAs; OECD; Urbanization